2019
DOI: 10.17582/journal.aavs/2019/7.5.397.404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ginger and Garlic Supplementation on Growth Performance, Whole Body Composition and Oxidative Stress in the Muscles of Nile Tilapia (O. Niloticus)

Abstract: An experiment was conducted to determine the impact of using garlic and ginger powder on growth performance, body composition, lipid peroxidation and antioxidant enzymes activities in muscle tissues of Nile tilapia fingerlings. Three isonitrogenous (32%) and isocaloric (3000 kcal DE) diets were formulated , control basal diet, diet supplemented with 1.5% ginger powder, other diet supplemented with 1.5% garlic powder and fed to the fish for sixty days at 3% body weight. No significant effects were found in fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 0 publications
4
19
2
Order By: Relevance
“…The findings of the present study on growth performances and feed utilization revealed that C. gariepinus fry fed with basal diet supplemented with either garlic powder or ginger powder showed better growth and feed utilization in term of weight gain, length gain, specific growth rate, feed intake, feed conversion ratio as well as protein efficiency ratio compared to control diet. On contrary to the results obtained by Mahmoud et al [27] who found poor growth and feed utilization in term of specific growth rate and feed conversion ratio after feeding Oreochromis niloticus fingerlings for 60 days with 1.5% ginger and garlic compared to basal control diet, the results of the present study are in accordance with those obtained by Jahanjoo et al [44] who recorded better growth performance and feed utilization in Sobaity Sea Bream (Sparidentex hasta) fry fed with basal diet containing 1% of garlic and ginger respectively for 8 weeks. In addition, the highest values of growth performance and feed utilization were observed in fish fry fed the basal diet containing 1% of both ginger and garlic compared to control diet and even diet with 2% of plant material.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The findings of the present study on growth performances and feed utilization revealed that C. gariepinus fry fed with basal diet supplemented with either garlic powder or ginger powder showed better growth and feed utilization in term of weight gain, length gain, specific growth rate, feed intake, feed conversion ratio as well as protein efficiency ratio compared to control diet. On contrary to the results obtained by Mahmoud et al [27] who found poor growth and feed utilization in term of specific growth rate and feed conversion ratio after feeding Oreochromis niloticus fingerlings for 60 days with 1.5% ginger and garlic compared to basal control diet, the results of the present study are in accordance with those obtained by Jahanjoo et al [44] who recorded better growth performance and feed utilization in Sobaity Sea Bream (Sparidentex hasta) fry fed with basal diet containing 1% of garlic and ginger respectively for 8 weeks. In addition, the highest values of growth performance and feed utilization were observed in fish fry fed the basal diet containing 1% of both ginger and garlic compared to control diet and even diet with 2% of plant material.…”
Section: Discussioncontrasting
confidence: 65%
“…Although it has been reported in previous studies that garlic and ginger have been found to strengthen immunity and uplift health status, enhance growth and flesh quality in freshwater fish like common carp (Cyprinus carpio), tilapia (Oreochromis niloticus) and African catfish (Clarias gariepinus) [7] [26] [27], studies in respect to their efficacy in African catfish in general and during nursery operations in particular are inadequate. Hence, the aim of the present study was to evaluate the effect of garlic and ginger powders as feed additive on growth criteria, feed nutrients utilization and whole-body composition in African catfish fry.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study showed a significant increase of plasma SOD and catalase activities and a significant decrease of plasma malondialdehyde level in rainbow trout fed diets supplemented with microencapsulated garlic extract. Similarly, previous investigations reported that dietary garlic can improve the antioxidant status of O. mykiss, Cyprinus carpio and O. niloticus as evidenced by decreased thiobarbituric acid in serum and tissues (Mohebbi et al 2012;Naeiji et al 2013;Mahmoud et al 2019). Kumar et al (2009) reported that garlic extract reduces oxidative stress caused by cadmium in freshwater catfish (Clarias batrachus).…”
Section: Discussionmentioning
confidence: 69%
“…Ginger antioxidant capacity was previously demonstrated for O . niloticus fed 10 and 15 g/kg of GgP (Antache et al, 2013; Mahmoud et al, 2019). Sahan et al (2016) also observed that GgP at 5 g/kg and 10 g/kg enhanced SOD and CAT activities in liver, gill and gut and decreased MDA concentration on Nile tilapia infected with A .…”
Section: Discussionmentioning
confidence: 99%